2011
DOI: 10.1007/s11605-011-1502-1
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Outcomes from Pancreatic Resection: a Review and Meta-analysis

Abstract: BMI increases the operative complexity of pancreatectomy. However, with aggressive peri- and post-operative care, increases in BMI-associated morbidity and mortality may be mitigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 86 publications
2
21
2
Order By: Relevance
“…Majumder et al 42 showed positive correlation between obesity and mortality in PC patients in Western but not Asia-Pacific populations. Ramsey and Martin 43 reported that BMI increases the complexity in resection of PC, but aggressive para-operative care could mitigate obesity-associated morbidity and mortality. These two results imply that there is no “universally applicable” relationship between BMI and prognosis in PC and the relationship has to be individually evaluated according to clinical or demographical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Majumder et al 42 showed positive correlation between obesity and mortality in PC patients in Western but not Asia-Pacific populations. Ramsey and Martin 43 reported that BMI increases the complexity in resection of PC, but aggressive para-operative care could mitigate obesity-associated morbidity and mortality. These two results imply that there is no “universally applicable” relationship between BMI and prognosis in PC and the relationship has to be individually evaluated according to clinical or demographical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Median EBL for the (NF) cohort was 250 ml, and MVA confirmed the independent protective effect of minimizing blood loss on the occurrence of POPF post-RPD. Although BMI was not included as a major risk factor in the Braga and Callery scores, obesity is a welldefined risk factor for post-PD complications in general and POPF in particular [38][39][40][41]. Patients with larger BMI harbor more pancreatic steatosis, a finding that may increase the risk of POPF as described by Mathur et al and Gaujax et al [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The association between obesity and survival from these studies has been mixed [13, 17, 19, 20] and may be explained by a variety of factors including small study size, assessment of outcomes unrelated to obesity, and heterogeneity in criteria for study enrollment and in BMI measures [24]. Additionally, many of these studies were designed to determine how obesity at time of surgery affected patient surgical outcome(s), rather than to assess the relationship between usual adult obesity (or obesity at a specific age) and survival duration in pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%